Global burden of maternal hypertensive disorders (1990–2045): trends, regional disparities, and causal links to occupational exposures - Junpeng Xiong; Shuwen Chen; Han Wang; Xiaonan Yang; Xinyi Chen; Binquan You; Ronghui Yu (BMC Pregnancy and Childbirth)
Abstract Background Maternal Hypertensive Disorders (MHD), encompassing gestational hypertension, chronic hypertension, preeclampsia, and eclampsia, which was a significant contributor to maternal morbidity and mortality, particularly in regions with lower socioeconomic status. Methods Using data from the 2021 Global Burden of Disease (GBD) study, we analyzed the burden of MHD globally. We used the slope index and concentration index to measure cross-country inequality in MHD burden, and employed a Bayesian age-period-cohort (BAPC) model to project the burden from 2022 to 2045. Additionally, we conducted a two-sample Mendelian randomization (MR) analysis based on genome-wide association study (GWAS) to investigate potential causal relationships between occupational exposures and MHD. Results Overall, the global incidence, prevalence, mortality, and DALYs for MHD have declined. However, incidence and prevalence rose in Central Asia, Eastern Europe, and Western Europe, while the Caribbean increasing in mortality and DALYs. Iron deficiency emerged as the leading risk factor. Significant SDI-related inequalities in MHD burden were observed, especially in lower SDI countries. Projections suggest ongoing reductions in MHD burden through 2045. MR results revealed a significant causal link between frequent exposure to chemical or other fumes in the workplace and MHD, while no clear causal relationships were identified for particulate matter or other assessed exposures. Conclusions Although the global MHD burden is decreasing, marked regional disparities persist. Efforts focusing on addressing iron deficiency, improving nutritional support, and mitigating occupational exposures may further reduce the burden. Strengthening maternal healthcare services—especially in low-SDI will be crucial for achieving sustainable declines in MHD worldwide.